Pelatihan AI Marketing bagi Pelaku UMKM Ikan Asin untuk Mendukung Transformasi Digital Usaha di Kelurahan Keteguhan, Kecamatan Teluk Betung Timur, Kota Bandar Lampung - Cahyani Pratisti; Yusminar Wahyuningsih; Rina Milyati Yuniastuti; Jhon Nasyaroeka (Universitas Pahlawan Tuanku Tambusai, 2026)
Small and Medium Enterprises (SMEs) producing salted fish and anchovy products in Keteguhan Village, Teluk Betung Timur District, Bandar Lampung, face several challenges, including low digital literacy, limited promotional content creation skills, and minimal utilization of Artificial Intelligence (AI) in marketing activities. This community service program aimed to enhance the digital competencies of fishermen, fishermen’s wives, and fisheries-based SME owners through AI Marketing training. The program employed community education, technology transfer, hands-on training, and mentoring approaches utilizing ChatGPT, Canva AI, and social media platforms. A total of 30 participants were involved in the program. Evaluation was conducted through pre-tests, post-tests, observations, and interviews. The results indicated a significant improvement in participants’ competencies, with the Paired Sample t-Test showing a significance value of 0.000 (p 0.05). The program also generated practical outputs, including business social media accounts, AI-based promotional posters, marketing captions, and promotional videos. These findings demonstrate that AI Marketing can effectively support digital transformation and enhance the competitiveness of fisheries SMEs in coastal communities.